2021
DOI: 10.1007/978-3-030-55686-0
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Brass Instruments

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…According to the so-called Bouasse-Benade prescription [58][59][60], near perfect inharmonicity between the resonances is cited as a condition for good playability of the instrument. This prescription is also discussed in recent studies [9,61]. On the saxophone, experimental studies using an artificial mouth have shown that varying inharmonicity greatly affects regime production [2,8].…”
Section: Effect Of the Resonator's Inharmonicity On Regime Productionmentioning
confidence: 89%
“…According to the so-called Bouasse-Benade prescription [58][59][60], near perfect inharmonicity between the resonances is cited as a condition for good playability of the instrument. This prescription is also discussed in recent studies [9,61]. On the saxophone, experimental studies using an artificial mouth have shown that varying inharmonicity greatly affects regime production [2,8].…”
Section: Effect Of the Resonator's Inharmonicity On Regime Productionmentioning
confidence: 89%
“…The magnitude of the input impedance exhibits a series of "strong" resonances (1-9), followed by "weak" resonances (10)(11)(12). Each of these resonances, except the first one, allows the musician to play a note with a pitch close to the resonance frequency (such a note is referred to as a "natural note") [26]. The 12th resonance peak corresponds to a F5 note.…”
Section: Approximation Of the Input Impedance Of A Bass Trombonementioning
confidence: 99%
“…Of particular interest is the influence of the musician's control parameters on the oscillation frequency (linked to the intonation), and the minimum mouth pressure required to achieve auto-oscillations (related to the ease of playing). Indeed, it is assumed here that the musician's feeling of ease of playing partly relies on the threshold blowing pressure: the higher the latter, the higher the physical effort the player has to make to play a note [1]. In practice, the musician can play several notes without depressing any valves in the case of a tuba, or moving the slide in the case of a trombone.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the musician can play several notes without depressing any valves in the case of a tuba, or moving the slide in the case of a trombone. These playing regimes are called the natural notes (B[1, B[2, F3, B[3, D4, F4,... in the case of a trombone or a euphonium for instance), and their frequencies are close to the resonance frequencies of the instrument as a whole, except for the lowest note playable (B [1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation